THE IMPACT OF ENVIRONMENTAL CONCERN, AND ENVIRONMENTAL ATTITUDE ON GREEN PRODUCT PURCHASE INTENTION - Ahmad Mustofa; Rinnanik Rinnanik (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Environmental pollution due to plastic bottle waste is still an important issue that has not been resolved until now in various cities in Indonesia, including . Plastic bottle waste is increasing in number along with the increasing use of plastic bottles for packaging of beverage products. This waste problem is also faced by the City of Bandar Lampung, which is the third largest waste producer in Sumatera. Efforts that can be made to overcome these problems are to manage and reduce them. The purpose of this study to examine and analyze the effect of environmental concern, and environmental attitude on green product purchase intention. This research method uses a quantitative approach. The population of this study were users/consumers of Tupperware drinking bottles in Bandar Lampung. The samples of this study were men and women, at least 17 years old, had used Tupperware drinking bottles for at least 1 year. The sampling technique used was the purposive sampling technique. Data collection techniques using a questionnaire. The data analysis technique with Structural Equation Modeling (SEM) AMOS.. The results show that environmental concern does not affect the purchase intention of green products, but environmental attitudes had affect to green product purchase intention. Keywords: Environmental Concern, environmental attitude, green product purchase intention, Structural Equation Modeling